An Adaptive Virtual Impedance-Based Controllably Inductive Power Filtering System - Wang, Shaoyang; Li, Yong; Lin, Gang; Lin, Jinjie; Fang, Hao; Miao, Ruiwen (Proceedings - International Conference on Harmonics and Quality of Power, 2024)
To overcome the limitations of conventional inductive power filtering as a passive filtering approach, in this paper, an adaptive virtual impedance-based controllably inductive power filtering system (AVI-CIPFS) is proposed. This system consists of an inductive filtering transformer, an LC-filter bank, and an active inverter. Assisted by the multi-objective control strategies developed, it can dampen the resonance between passive filters and grid-side impedance, manipulate power factor, and perform multiple harmonic mitigation simultaneously. In addition, using the quasi-PR controller with frequency division detection, it also removes the coupling between active and reactive components in the dq0 frame, greatly reducing the steady-state current tracking errors. Experimental results demonstrate the practicality of this proposal.